Ana Fernández-Cebrián. Fables of Development: Capitalism and Social Imaginaries in Spain (1950-1967). Liverpool UP, 2023. - Miguel Caballero (Studies in 20th & 21st Century Literature, 2025)
Review of Ana Fernández-Cebrián. Fables of Development: Capitalism and Social Imaginaries in Spain (1950-1967). Liverpool UP, 2023, x + 210 pp.
Keywords: Spain; Franco; capitalism